2021
DOI: 10.1007/s10311-021-01198-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation of persistent free radicals in sludge biochar by hydrothermal carbonization

Abstract: The uses of biochar as soil fertilizer can offset global warming and reduce dependence on limited mineral resources in the future circular economy, yet biochar may contain contaminants that can ultimately enter the food chain. In particular, persistent free radicals are emerging contaminants previously detected in biochar but underlying mechanisms of radical formation are not yet established. Here we studied radical generation during hydrothermal carbonization of waste sludge at 160-220 ºC for 0.5-2 h with sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In addition, significant increases in the abundance of lysophospholipid species such as LPA (18:1), LPA (20:4), LPC (0:0/16:0), LPC (22:6), LPE (18:0/0:0), LPE (0:0/16:0), and LPE (0:0/18:0) were found during the spray-drying treatment in the present study. Some studies have reported an increase in the abundance of some lysophospholipid species in spray-dried processed food fractions, but the corresponding mechanisms of occurrence remain unclear ( Ali et al, 2018 ; Tang et al, 2021 ). Egg yolk is rich in endogenous lipases such as phospholipase and neutral lipase ( Parchem and Bartoszek, 2016 ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, significant increases in the abundance of lysophospholipid species such as LPA (18:1), LPA (20:4), LPC (0:0/16:0), LPC (22:6), LPE (18:0/0:0), LPE (0:0/16:0), and LPE (0:0/18:0) were found during the spray-drying treatment in the present study. Some studies have reported an increase in the abundance of some lysophospholipid species in spray-dried processed food fractions, but the corresponding mechanisms of occurrence remain unclear ( Ali et al, 2018 ; Tang et al, 2021 ). Egg yolk is rich in endogenous lipases such as phospholipase and neutral lipase ( Parchem and Bartoszek, 2016 ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to EPFRs in biochars derived from lignocellulosic biochars (Table S1 †), data in biochars derived from non-lignocellulosic biomass are very limited. [19][20][21] Sludge is a typical non-lignocellulosic biomass and sludge-based biochars receive widely attention in soil remediation, wastewater treatment, chemical catalysis, and so on, 22,23 but there were limited investigations on EPFRs in sludge-based biochars. 24 For example, the g-values of PFRs in sludge-based pyrobiochars were reported, but the spin concentrations of PFRs were not offered.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low activity of Mn-based mullite has been the main problem limiting the application of zinc–air batteries. In the current study, increasing oxygen defects, controlling morphology, metal ion doping, and compounding with carbon materials , are commonly used to optimize the performance of catalysts. It has been reported that Zhao et al introduced a perovskite structure in SmMn 2 O 5 by a one-step co-precipitation method, using the interfacial effect between SmMn 2 O 5 and perovskite to increase electron transport for improving the catalytic performance of the catalyst.…”
Section: Introductionmentioning
confidence: 99%